Deviant behavior of minors (moral and ethical aspect) - Koval, I. M. (Аналітично-порівняльне правознавство, 2025)
The article is devoted to the moral and ethical aspects of deviant behavior of minors, which is formed under the influence of external and internal factors, such as deformed socialization of the person. During martial law in Ukraine, juvenile prevention bodies, services for working with minors, educational institutions must conduct preventive work with minors to prevent the development of deviant behavior, which can manifest itself as both psychological and emotional and physical deviations from the socially acceptable norm. It is emphasized that it is important to provide psychological and legal assistance to minors who have been directly affected by military actions (lived in temporarily occupied territories or zones of active hostilities, suffered the loss of loved ones, belong to the category of internally displaced persons, etc.). It was found that each person has his own level and indicator of acceptable behavior in society, but general moral and ethical norms require compliance with the standards of coexistence of individuals in society based on respect for the rights and freedoms of each member of society. It is necessary to form moral and ethical values from early childhood. Such an approach will contribute to the value socialization of minors and their further lawful development. Attention is focused on the fact that conformism, innovation, ritualism, escapism (retreatism), rebellion (radicalism) as the main types of deviant behavior do not exist separately from the others. As a rule, manifestations of each type are observed in a person, but one of them prevails. The absence of social and value guidelines, passive social behavior contributes to the development of unlawful manifestations of a person’s life. It is noted that during military operations, the problem of maintaining a stable psychological and moral state of minors is very relevant. The influence of hostile propaganda services through virtual networks can lead to asocial behavior. Today, social services and law enforcement agencies must actively work to prevent the negative impact of all resources on the consciousness and behavior of children. Constant stress from the realities of military operations (air raids, shelling, deaths) provokes self-destructive behavior of a person. A minor may choose the wrong path to overcome psycho-emotional stress through the use of prohibited substances, gambling, suicide.